GBSAR-Proc - Elgy, James (Cranfield University, 2019)
The GBSAR-Proc Python package is designed to load and process data gathered from Cranfield University's ground based Synthetic Aperture Radar (SAR) system. Included in the package are a series of classes designed to manipulate raw data, process it into range profiles and finally use the Backprojection Algorithm to plot high quality near-field SAR images. In addition to the more common planar SAR images, there is functionality to both generate and plot volumetric SAR images, formed on either the CPU or GPU.
Keywords: 'RADAR'; 'SAR'; 'python package'; 'Photogrammetry and Remote Sensing'